ATO/Polyaniline/PbS Nanocomposite as Highly Efficient Photoelectrode for Hydrogen Production from Wastewater with Theoretical Study for the Water Splitting - Mohammed A. H. Khalafalla; N. M. A. Hadia; Asmaa M. Elsayed; Mansoor Alruqi; Wassim El Malti; Mohamed Shaban; Mohamed Rabia (Adsorption Science & Technology)
Polyaniline-assisted deposition of PbS is carried out on antimony tin oxide (ATO) glass for ATO/PANI/PbS composite formation. The deposition of PbS was carried out inside and outside the polymer chains using the ionic adsorption deposition process. Various analyses were conducted to confirm the chemical structure and morphological, optical, and electrical properties of the resulting composite. TEM and SEM analyses demonstrated the spherical shape of PbS particles inside and outside the PANI network with more dark or white color, respectively. Moreover, the ImageJ program confirmed the composite formation. The XRD characterization showed the shifts in the PANI peaks after the composite formation with the appearance of a new additional peak related to PbS nanoparticles. The optical analyses were massively enhanced after the composite formation with more broadening in the Vis region at 630 nm, in which there was more enhancement in the bandgap that reached 1.5 eV. The electrode application in the H2 generation process was carried out from wastewater (sewage water, third treatment) without any additional sacrificing agent. The electrode responded well to light, where the current density (Jph) changed from 10-6 to 0.13 mA.cm-2 under dark and light, respectively. The electrode had high reproducibility and stability. The numbers of generated H2 moles were 0.1 mmol/cm2.h. The produced ΔH∗ and ΔS∗ were 7.3 kJ/mol and 273.4 J/mol.K, respectively. Finally, the mechanism explains the H2 generation reaction using three-electrode cell.